Coarse lattice results for glueballs and hybrids - PEARDON, MICHAEL JAMES (Elsevier, 1998)
A review of new results from lattice simulations of glueballs and heavy-quark hybrid mesons is presented.
PUBLISHED
Keywords: Pure & Applied Mathematics